Dietary antioxidants, supplements, and risk of epithelial ovarian cancer. - Fleischauer AT; Olson SH; Mignone L; Simonsen N; Caputo TA; Harlap S (Nutrition & Cancer, 2001)
Several studies of dietary and serum antioxidant micronutrients (vitamins A, C, and E and beta-carotene) suggest that higher levels may be protective for ovarian cancer. None of these has examined supplements. We used a food frequency questionnaire and additional questions on supplements to study 168 histologically confirmed epithelial ovarian cancer cases, 159 community controls, and 92 hospital-based controls. Antioxidant consumption from diet or supplements was calculated in milligrams or international units per day. In multivariate analyses using only community controls, the highest levels of intake of vitamins C and E from supplements were protective: odds ratio (OR) = 0.40 [95% confidence interval (CI) = 0.21-0.78] and OR = 0.33 (95% CI = 0.18-0.60), respectively. Consumption of antioxidants from diet was unrelated to risk. In analyses combining antioxidant intake from diet and supplements, vitamins C (> 363 mg/day) and E (> 75 mg/day) were associated with reduced risks: OR = 0.45 (95% CI = 0.22-0.91) and OR = 0.44 (95% CI = 0.21-0.94), respectively. Results were similar, with some attenuation toward the null, in analyses combining both control groups. The levels of vitamins C and E associated with the protective effect were well above the current US Recommended Dietary Allowances. These findings support the hypothesis that antioxidant vitamins C and E from supplements are related to a reduced risk of ovarian cancer.